Renal Allograft Biopsy Findings in HLA Identical Renal Transplant Recipients. (July 2018) - Mubarak, Muhammad; Zafar, Mirza Naqi; Aziz, Tahir; Abbas, Khawar; Rizvi, Adibul Hasan
Abstract : Objectives: HLA identical transplants are immunologically privileged and have the best graft survival in both deceased and living donor settings, yet the grafts do fail. This study describes the causes of graft failure in HLA identical transplants as detected on renal allograft biopsies. Patient and Methods: Between 1992 and 2012, 3749 live-related transplants were performed at our center. Of these, 756 (20%) were HLA identical. Immunosuppression comprised of triple drug regimen: CyA/AZA or Tacrolimus/MMF with steroids. Graft dysfunction episodes were confirmed by biopsy, when indicated. Graft biopsies were reported according to Banff classification. All recipients were followed-up lifelong, where all treatment is provided free including immunosuppression drugs. Results: In the follow-up period of 4 to 20 years, 160/756 (21%) of the identical grafts were lost with 5, 10, 15 years survival rates of 85%, 68% and 60% respectively. A comparison of those who lost grafts (Group A, n=160) vs. those who maintained function (Group B, n=596) showed that in Group A, donors were older (35±9 vs. 32±9, p=0.001), GFR was lower (97±24 vs. 110±23 ml/min, p=0.001) and there were more females (46% vs. 33%, p=0.031). Among recipients in group A, there were more females (25% vs. 18%, p=0.03) and hypertensives (60% vs. 49%, p=0.04). Acute rejection rates in group A were higher (13% vs. 4.8% p=0.001), as was cyclosporine toxicity on biopsy (14% vs. 11%, p=0.20) and recurrence of original disease (9% vs. 4%, p=0.03) as compared to Group B. Of the 160 grafts lost, 24% were functioning but lost due to death of recipients, 7% were lost due to recurrence, 7% to infection in the graft, 6% to acute rejection and 50% to interstitial fibrosis/tubular atrophy (IFTA). Conclusion: HLA identical grafts have superior survival due to immunological privilege, but are susceptible to non-immunological injury, including CyA toxicity.